Implementation of Total Quality Management in the Malaysian Automotive Vendors - Kasolang, Salmiah (2001)
This study is on the implementation of TQM in the Malaysian Automotive Industry focusing at vendor quality management practices. It is meant to gauge how vendors are doing collectively in their quality pursuit, specifically in TQM implementation. The research methodology involved a survey using a set of established questionnaire addressed to quality personnel and other equivalent officers. The questionnaire gauged the various aspects of quality practices. The design of the questionnaire was based mainly on the seven criteria of the Malcolm Baldrige National Quality Award. The layout of the study consists of four phases captured in PDCA Cycle: Plan, Do, Check, and Act. The results highlight vendor performance in seven quality criteria and nine groups of quality implementation initiatives. Some of the key findings indicate that a majority of vendors isolated ISO 9000 certification from TQM implementation. Ninety three per cent of vendors are certified with ISO 9000. Conversely, only about thirty one per cent of vendors claimed to have TQM introduced in their organization. Based on the overall results, it could be concluded that a majority of the vendors have introduced TQM in one form or the other. However, not many of them realize it because they lack the TQM understanding. Therefore, an improvement framework is suggested to improve the TQM understanding as well as other weaknesses identified in the study. The framework will also help to strengthen some of the current quality practices among vendors. The suggested improvement framework of the TQM implementation has three major segments: (1) assessment prior to an improvement exercise, (2) major elements in TQM improvement framework, and (3) assessment after an improvement exercise. SWOT analysis and PDCA cycle are two of the main elements in the suggested improvement framework.